DEVELOPING PARTICIPATIVE AND COLLABORATIVE LEARNING MODEL OF SCIENTIFIC WRITING SKILL AS A WAY OF PROMOTING STUDENTS’ SOCIAL AND EMOTIONAL INTELLIGENCE - Supriyadi Supriyadi; Muslimin Muslimin (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2019)
The purpose of this research is to develop a learning model of participative and collaborative scientific writing skill to promote students’ social and emotional intelligence. This research is also intended to produce skilled graduates in terms of scientific writing and to enable the graduates to possess social and emotional intelligence. This is developmental research. In order to achieve research objectives, a developmental model of A Recursive Reflective Design and Development Model (R2D2) and Research Development Research (RDR) are used. The data consist of qualitative data and quantitative data. The technique used to analyze the data involved domain analysis techniques to analyze the qualitative data, and statistical analysis techniques for the  quantitative data. The result of this developmental research is a participative and collaborative learning model of scientific writing to develop students' social and emotional intelligence. This research also has delivered a distinctive developmental product compared to a conventional learning model, including concept orientation, concept exploration, concept interpretation, concept application, and evaluation. In addition, a participative and collaborative learning model of scientific writing skills should be developed continuously and be promoted to students who are interested in scientific writing, as it can be used to develop students' social and emotional intelligence. On the other hand, lecturers can utilize this product to improve the quality of the learning process, the results of learning scientific writing and developing students' social and emotional intelligence in which this model can be employed as an alternative model to enrich the learning process.